Policy Implementation To Arrange The Street Vendors By The Government of Denpasar City, Bali Province - Anak Agung Gede Oka Wisnumurti; Ni Nyoman Reni Suasih (Iapa Proceedings Conference, 2018)
Street vendors are informal types of work (small businesses) that arise primarily in urban areas, carried out by low-income people (daily salaries), have limited capital, and consist of only one worker (self employed). The presence of street vendors in various major cities in Indonesia, including in Denpasar City, has become a dilemma that creates pro-contra, and has the potential to clash between citizens and officials of government. This is because street vendors sell their wares in public places that are considered strategic, thus disrupting public order, and other public peace. On the other hand, according to one of the SDG’s programs, the government has an obligation to realize decent work for everyone. In the effort of structuring street vendors, as well as helping small traders of economic actors in the informal sector, the government of Denpasar City issues Denpasar City Local Law No. 2 of the year 2015 about Street Vendors. Therefore, an analysis is needed to find out the implementation of Denpasar City Local Law No. 2 of the year 2015, as well as to find out the supporting factors and inhibiting factors of its implementation. This research is a qualitative descriptive study, where the data obtained through the process of observation, interviews, and documentation studies. Selection of informants through purposive sampling technique, and data analysis techniques using Merilee S. Grindle's theory of policy implementation and contingency theory by James Lester. The results of the analysis show that the implementation of Denpasar City Local Law No. 2 of the year 2015 for arranging street vendors is still faced with several obstacles such as: lack of location according to allotment, lack of adequate budget, evaluation that is rarely done, and sanctions that are not in accordance with what is written in the Regional Regulation and the lack of understanding of street vendors on the local law. An interesting finding is that it turns out that governemtn of villages and custom village have an important role in organizing street vendors in their areas.